The Graduates’ 21st Century Skills Performance at Workplace: A Challenge and Reflection for Universities in Revolution Industry 4.0 Era - Hadiyanto, Hadiyanto; Sulistyo, Urip; Noferdiman, Noferdiman (Technium Social Sciences Journal, 2022)
Revolution industry 4.0 expects universities to endow graduates with 21st-century skills performance at the workplace. The 21-century skills are categorized into Soft Skills, Hard Skills, and Competitiveness (SHC). These skills enable to the promotion of faster institutional enterprise and industrial growth as well as advancement in the economic sector. Therefore, the purpose of this study was to investigate how graduates’ SHC performance skills contribute to productivity in the workplace in Indonesia. The survey questionnaire was used to collect data from government institutions and enterprises, including industries. The questionnaires were categorized into three, including Non-state-enterprises, State-Owned enterprises, and government institutions, though out of 500 only 162 were returned. The results showed that graduates’ performance of soft skills, hard skills, competitiveness, and overall SHC were at a medium level. An inferential analysis found that the social science group exhibited better soft skills, competitiveness, and overall SHC performance than the pure science group with no difference in hard skills performance. Graduates from the none-state-enterprises and state-owned enterprises group showed better SHC performance than those working directly for the government. Moreover, none-state-enterprises had a higher SHC performance than graduates from state-owned enterprises. However, there was no correlation between soft graduate skills, competitiveness, and overall SHC performance and graduates’ CGPA. There was a relatively smaller correlation between hard skills performance and graduates’ CGPA. Therefore, university graduates are ill-prepared to meet the SHC performance needed at the workplace. The current Higher education curriculum, though built to emphasize SHC for a decade, did not achieve its purpose to produce quality graduates due to poor implementation.